Pharmacodynamic Mismatch in Adductor Canal Blockade: Dexamethasone Phosphate (Rapid-Salt) Outperforms Methylprednisolone Acetate (Depot-Suspension) for Early Mobilization - Beny Firmansyah; Taufiq Agus Siswagama; Buyung Hartiyo Laksono (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: The motor-sparing adductor canal block (ACB) is central to enhanced recovery after surgery (ERAS) protocols for knee surgery. Corticosteroid adjuvants are used to prolong analgesia, but a direct comparison of perineural Dexamethasone and Methylprednisolone is lacking. This study aimed to observe real-world associations between these adjuvants, postoperative pain, and functional recovery. Methods: This analytical, prospective, observational cohort study was conducted at a tertiary hospital from November 2024 to April 2025. Fifty-three patients undergoing knee surgery under subarachnoid anesthesia were enrolled. Following surgery, patients received an ultrasound-guided ACB with 20 mL of Ropivacaine 0.5% combined with either Dexamethasone 10 mg (n=24) or Methylprednisolone 60 mg (n=29), based on the attending anesthesiologist's preference. The primary functional outcome was time to mobilization. Secondary outcomes included Numerical Rating Scale (NRS) pain scores at 12, 24, and 48 hours. Results: A significant association was observed for the primary functional outcome: 87.5% of the Dexamethasone cohort mobilized within 24 hours, versus 62.1% of the Methylprednisolone cohort (p = 0.037). This functional advantage was congruent with a superior early analgesic profile; the Dexamethasone group reported significantly lower mean NRS scores at 12 hours (2.71 ± 0.81 vs. 3.86 ± 1.13; p < 0.001) and 24 hours (2.17 ± 0.56 vs. 3.24 ± 0.69; p < 0.001). A significant baseline difference in age distribution (p = 0.009) was identified as a key variable. Conclusion: This study provides the first clinical comparison of a rapid-acting salt (Dexamethasone Phosphate) versus a depot-suspension (Methylprednisolone Acetate) as perineural adjuvants in ACB. The observed superior functional and analgesic profile of Dexamethasone aligns with its pharmacokinetic properties, suggesting a pharmacodynamic mismatch between slow-release formulations and the pathophysiology of acute 24-hour postoperative pain.